2021
DOI: 10.3389/fphar.2021.779779
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Major RNA Adenosine Modifications in Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer malignancy worldwide and is known to have poor prognosis. The pathogenesis behind the development of HNSCC is not fully understood. Modifications on RNA are involved in many pathophysiological processes, such as tumor development and inflammation. Adenosine-related RNA modifications have shown to be linked to cancer and may play a role in cancer occurrence and development. To date, there are at least 170 different chemical RNA modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 159 publications
0
4
0
Order By: Relevance
“…Growth differentiation factor-10 (GDF10), also known as BMP3b, is a tumor suppressor that belongs to the transforming growth factor-b (TGF-b) superfamily ( Cheng et al, 2016 ). CIB1, PIM3, SLC16A3, VOPP1, BMP4, TIGIT, ADAR, and LRRN4CL are studied as upregulated genes in various cancer types such as squamous carcinoma cells, breast cancer, head and neck squamous cell carcinoma, and pancreatic cancer ( Baras et al, 2011 ; Alarmo et al, 2013 ; Zheng and Tian, 2014 ; de Jong et al, 2018 ; Notarangelo, 2018 ; Broutian et al, 2020 ; Yu et al, 2020 ; Huo et al, 2021 ; Wen et al, 2021 ; Yang et al, 2022 ). A complex that is important in the keratinocyte-intrinsic immune response to human papillomaviruses (-HPVs) is formed when CIB1 interacts with the EVER1, and EVER2 proteins ( de Jong et al, 2018 ; Notarangelo, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growth differentiation factor-10 (GDF10), also known as BMP3b, is a tumor suppressor that belongs to the transforming growth factor-b (TGF-b) superfamily ( Cheng et al, 2016 ). CIB1, PIM3, SLC16A3, VOPP1, BMP4, TIGIT, ADAR, and LRRN4CL are studied as upregulated genes in various cancer types such as squamous carcinoma cells, breast cancer, head and neck squamous cell carcinoma, and pancreatic cancer ( Baras et al, 2011 ; Alarmo et al, 2013 ; Zheng and Tian, 2014 ; de Jong et al, 2018 ; Notarangelo, 2018 ; Broutian et al, 2020 ; Yu et al, 2020 ; Huo et al, 2021 ; Wen et al, 2021 ; Yang et al, 2022 ). A complex that is important in the keratinocyte-intrinsic immune response to human papillomaviruses (-HPVs) is formed when CIB1 interacts with the EVER1, and EVER2 proteins ( de Jong et al, 2018 ; Notarangelo, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a significant correlation between increased ADAR expression and poorer survival outcomes in esophageal squamous cell carcinoma [ 12 , 36 ] and human hepatocellular carcinoma [ 10 ]. In this study, we demonstrated that total ADAR mRNAs and typical transcripts ( p110 ) were highly expressed in CRC compared with adjacent paracancerous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Growth differentiation factor-10 (GDF10), also known as BMP3b, is a tumor suppressor that belongs to the transforming growth factor-b (TGF-b) superfamily [42]. CIB1, PIM3, SLC16A3, VOPP1, BMP4, TIGIT, ADAR, and LRRN4CL are studied as upregulated genes [2,[43][44][45][46][47][48][49][50][51]. A complex that is important in the keratinocyte-intrinsic immune response to human papillomaviruses (-HPVs) is formed when CIB1 interacts with the EVER1, and EVER2 proteins [43,44].…”
Section: Discussionmentioning
confidence: 99%